Selling World Health Organization's Alcohol “Best Buys” and Other Recommended Interventions in an Urban Chinese Population: Public Acceptability of Alcohol Harms Reduction Strategies in Hong Kong - Yu, Jiazhou; Dong, Dong; Sumerlin, Timothy S.; Goggins, William B.; Feng, Qi; Kim, Jean H. (Frontiers in Public Health, 2022)
Background: To counter the harms caused by alcohol use, the World Health Organization (WHO) outlined a series of evidence-based recommendations, including the highly cost-effective “Best Buys” recommendations. While many Western countries have been actively introducing alcohol harms reduction strategies, it is unclear whether these cost-effective policies would be publicly acceptable in Asian regions with traditionally low alcohol consumption. This study examines the public acceptability of WHO-recommended alcohol harms reduction strategies in an Asian city with few extant alcohol regulations. Methods: A cross-sectional telephone survey of Hong Kong Chinese residents aged 18-74 (n=4000) was conducted from January to August 2018. Respondents were asked about their perceptions of various WHO-recommended strategies and consequences of their implementation. After reducing the strategies into several policy categories by principal component analysis, multivariable linear regression was performed to identify factors associated with endorsement of the various policies. Results: Among the “Best Buys”, introduction of moderate beer/wine taxes (68.7%) and shortened alcohol retail hours (51.9%) were the most supported while bans on event sponsorships (19.5%) and public drinking events (17.7%) were the least popular. Strategies targeting young drinkers were particularly highly-supported. Males, younger adults, non-abstainers, and those who believed in drinking’s social benefits were less likely to endorse stringent control measures (p<0.05). Adults with higher household income were less supportive, partially due to concerns about infringements on local economy, lifestyles, and economic freedom. Women and older people were generally more supportive, partially because they perceived these policies would lower alcohol-related harms. Conclusion: In order to reduce barriers to implementing WHO-recommended strategies in the region, it is imperative to increase awareness of alcohol-related harms and to strengthen beliefs in the effectiveness of these countermeasures, especially among men, young adults, and drinkers.